Clinical application of endoscopic diaphragmotomy and dilation in a congenital duodenal diaphragm - Sun, Song; Zheng, Shan; Wu, Jie; Tang, Zifei; Shen, Chun; Chen, Gong; Dong, Kuiran (Frontiers in Pediatrics, 2024)
Background: Congenital duodenal diaphragm (CDD) is a rare cause of duodenal obstruction in infants and children. The traditional approach to treatment has been surgical intervention by either excision and duodenoplasty or with bypass via a duodeno-duodenostomy, which is invasive and has the risk of anastomotic leakage.Aims: To summarize the key points of differential diagnosis and treatment of CDD under gastroscopy, and to evaluate its efficacy and safety.Methods: The clinical data of patients with duodenal obstruction diagnosed and treated by gastroscopy in our hospital between January 2019 to December 2022 were retrospectively analyzed. The gastroscopic features of CDD were summerized. The clinical outcomes of patients with CDD treated by gastroscopy were collected and investigated.Results: A total of 13 children with duodenal obstruction underwent gastroscopic examination and/or treatment, 10 of them were diagnosed as CDD, and 3 cases were finally diagnosed as annular pancreas. A dome-shaped structure during inspiration (9/10) and a guidewire that could be inserted through the opening into the distal lumen (6/10) were the gastroscopic features of the CDD, while the annular pancreas had none of these features. Ten patients, 4 males and 6 females with CDD were treated through endoscopic diaphragmotomy and dilation. The age and weight at operation was 15 days to 7 years (M: 2.25 years) and 2.85-22kg (M: 13.6kg) respectively. A total of 11 endoscopic operations were performed in 10 patients. The time of single operation was 15-55min (M: 38min). There were no complications such as bleeding, pneumoperitoneum and duodenal papilla injury during operation. Feeding was started 12-24 hours after surgery, and the patients were discharged 2-10 days (M: 7 days) postoperatively. The patients were followed up for 3-36 months (M: 17 months), and none of them had recurrence of vomiting. However, three showed recurrence of stenosis in UGI, one of which underwent partial diaphragm resection again 2 months after the primary treatment.Conclusions: The CDD can be confirmed by endoscopy based on its characteristic features. Endoscopic diaphragmotomy and balloon dilation are safe and effective, which can be a new option for minimally invasive treatment of CDD.